Avaliação da qualidade do sono em atletas de alta performance - Lima, Igor Francisco de [UNESP]; Messias, Lucas Hyan Costas [UNESP]; Linares, Stepanie Nogueira [UNESP]; Vanderlei, Franciele Marques [UNESP]; Pastre, Carlos Marcelo [UNESP]; Netto Junior, Jayme [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The sports environment is increasingly competitive and success is supported by an impeccable preparation. The quality of sleep is essential to good recovery and better sporting performance. The aim of this study was to investigate how sleep affects the emotional and psychological, and if it is able to change the performance of athletes during a competition. Twenty-six athletes (20 men and 6 women) athletics professionals with participation in National and International competitions of both sexes were evaluated from the Pittsburgh Sleep Quality Index. It follows that most of the evaluated athletes have an efficient sleep periods of pre competition and show great interference to sleep.

O ambiente esportivo está cada vez mais competitivo e o sucesso é sustentado por uma preparação impecável. A qualidade do sono é essencial para boa recuperação e melhor rendimento esportivos. O objetivo do presente estudo foi verificar quanto o sono interfere no emocional e no psicológico, e se o mesmo é capaz de alterar o rendimento dos atletas durante uma competição. Vinte e seis atletas (20 homens e 6 mulheres) profissionais de atletismo com participação em competições Nacionais e Internacionais de ambos os sexos foram avaliados a partir do Índice de Qualidade do Sono de Pittsburgh. Conclui-se, que a maioria dos atletas avaliados apresentam um sono eficiente em períodos de pré competição e não apresentam grandes interferências no sono.
Keywords: Sleep; Pittsburgh sleep quality index; Athletes; Sono; Índice de qualidade do sono de Pittsburg; Atletas